Eksistensi Pendampingan Teknologi Tumpang Sari Tanaman (Turiman) dalam Upaya Peningkatan Produksi Komoditas Sumber Pangan - Rima Purnamayani; Hari Hermawan (xxxx-xxxx, 2020)
Purnamayani R, Hermawan H.  2020.  Existence of intercropping technology (Turiman) assistance in efforts to improve the quality of food commodities. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xxx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The increase in food production can be implemented through the application of the pattern of intercropping (turiman), which can eliminate land use competition between plants and is a sustainable solution to the problem of land limitation. The objective of this study was to describe the existence of the assistance of intercroppping (Turiman) conducted by Assesment Institute for Agricultural Technology (AIAT), as an effort to increase the production of food source commodities. Survey research method by taking purposive samples of 32 respondents.  The data used scaling with Guttman scale, which was analyzed descriptively and tested with non-parametric statistics (Binomial Test).  The results of descriptive analysis showed that the assistance received by users in the field included the Technical Guidance of Turiman Technology, the competence of technology assistance by AIAT, the availability of variety displays on the location, the availability of agricultural machinery tools from government as well as the availabity of water resources .  The binomial test showed that the assistance  elements that have significant effect on improving the quality of food sources were: the availability of guidance on activities in the field both from AIAT and related agencies, the competency of human resources companions from AIAT team, training materials as needed, the availability of dissemination media and demonstrations plot, the display of commodity varieties in the field, superior seed assistance on time and utilized well, the availability of water sources and infrastructure that are utilized well, as well as the water management institution actively.